Opening FDN-museum, Alberdingh Thijmstraat 7, Amsterdam. C. Kitsz spreekt. Uit: De Arbeid 28 november 1925
Opening FDN-museum, Alberdingh Thijmstraat 7, Amsterdam. C. Kitsz spreekt. Uit: De Arbeid 28 november 1925.